KARAKTER FISIOLOGIS KLON KOPI ROBUSTA BP 358 PADA JENIS PENAUNG YANG BERBEDA - Ummi Sholikhah; Dena Munandar; Andri Pradana (Universitas Trunojoyo Madura, 2015)
Shade plants for coffee plantation generally use dadap, lamtoro andothers. Today there many change the use of shade plant from lamtoro to sengon because economic value and increasing demand for sengon wood. Due to thechanging in different type of shade plant cause affect on coffee plantationmicroclimate. On the coffee plantation also use some coffee clones. The differences type of shade and coffee clones can affect the differences physiological and morphological characters of coffee plant that affect the production.The aim of this research is expected to give information about physiological characters of robusta coffee clones in different shade plant, factors that affect the robusta coffee photosynthesis process, the relationship of photosynthesis with the production and robusta coffee clones that have high production. This research was conducted in coffee plantation at Sidomulyo village, the district of Silo, Jember regency located at a 560 meters above sea level. This research was done on May up to June 2011. The area determination method was chosen based on the consideration that Sidomulyo village is one of the popular coffee producer in Jember. The experiment used field experiment with the quadrant method use to observation and collect the data of 12 years old BP 358. The support parameter observed were light intensity, temperature, humidity and assessed fruit production. The data from the observation wereproduction branch than photosynthesis activity. The result showed coffee clones BP 358 with sengon shade had higher photosynthesis activity than lamtoro shade. The photosynthesis activity was more affected by the stomatal conductivity and the light intensity. Keyword: Physiological Characters, Coffee Clones BP 358, Types of Shade